Laryngeal cleft type IV: One pathology, two different presentations. (June 2018) - Hernández, Gabriel; Beauchamp-Pérez, Francis D.; González-Aquino, Carlos
Abstract: Laryngotracheoesophageal cleft is a rare congenital malformation where a communication exists between the aero-digestive tracts that is associated with high morbidity and mortality. In this case series, we describe our experience with two neonates evaluated in our institution with two diverse initial presentations and symptomatology of type IV laryngotracheoesophageal clefts. One patient presented with acute distress and respiratory failure due to bowel contents obstructing the trachea and the other presented with mild subcostal retractions and inspiratory stridor without overt respiratory failure. Most importantly, not every patient with type IV laryngotracheoesophageal clefts will present with fulminant respiratory difficulty. This prompted a literature review.